A comparison of beef flavor intensity among major muscles - Carmack, C.F.; Schwenke, J.R.; Kastner, Curtis L.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve muscles from eight Select/Choice grade steers were evaluated for beef flavor intensity, tenderness, and juiciness. Sample steaks were cut, and evaluation was performed by a five-member professional panel. The biceps femoris ranked highest in beef flavor intensity but was not different (P>.05) from the psoas major, gluteus medius, semimembranosus, and triceps brachii (scores of 7.8, 7.5, 7.4, 7.4, and 7.3, respectively). The rectus femoris, longissimus lumborum, serratus ventralis, infraspinatus, semitendinosus, deep pectoral, and supraspinatus were less intense in beef flavor (7.1, 7.1, 7.0, 6.8, 6.8, 6.7, and 6.6, respectively). The psoas major was most tender (P<.05) of all muscles, followed by the infraspinatus, longissimus lumborum, rectus femoris, and serratus ventralis, which were all similar (P>.05). Muscles from the chuck and loin were generally juicier than those from the round. This information may be useful in assisting processors in raw material selection for restructured, value-added processing and in assisting purveyors and consumers in selecting steaks and roasts for specific characteristics such as beef flavor intensity.
Keywords: Beef; Beef muscles; Flavor; Tenderness; Juiciness